The Effect of Religion Therapy on the Elderly Cognitive Status - Aloustani, Soudabeh (Journal of religion and health, 2021)
The elderly is passing from a stage to another new stage of life, with cognitive changes and a reduction in the physiological functions of this age. With increasing age, spiritual needs and attitudes increase. So, this study was conducted aimed to investigate the effect of group spiritual therapy on the cognitive state of the elderly. This experimental study was conducted in two experimental and control groups on 50 elderly people in Golestan Province in 2012, by simple random sampling. Data collection tool was Mini-Mental State Examination. In the experimental group, eight group therapy sessions were performed for 45-60 min a week twice. The data were analyzed by software SPSS-16 using descriptive statistics (mean score and SD) and inferential statistics (paired t test, independent t test and covariance test). Independent t test before the intervention in both groups showed no significant difference (P = 0.52). But this test showed a significant difference after the intervention (P < 0.01). Also, ANCOVA test showed a significant difference in both groups (η = 0.26) (P < 0/01) . Regarding the effect of group spiritual therapy on the cognitive state of the elderly, it can be used as a complementary, low cost and effective method for improving the cognitive state of the elderly. For this reason, it is recommended because spiritual therapy creates the concept and meaning of life and increases the life expectancy and quality of life in the elderly.